Paraffinic mineral oil lubrication for cold forward extrusion: Effect of lubricant quantity and friction - Mohd Hafis, Sulaiman; Mohd Ridzuan, Mohd Jamir; Nur Farahana, Ramli; Syahrullail, Samion (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/